The Effect of Informativeness, Entertainment, and Irritation on the Intention to Return to Tokopedia, Mediated by Attitude Toward the Tokopedia Mobile Application - Jonnathan Jordian; Kurnadi Gularso; Liem Bambang Sugiyanto; Michael Christian (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
This research aims to examine the effects of informativeness, entertainment, and irritation on users’ intention to return to Tokopedia, mediated by attitude toward the mobile application. In addition, this study compares the Technology Acceptance Model (TAM) and the Ducoffe Model in explaining attitude formation toward marketplace applications. TAM posits that attitude is formed after users gain experience through perceived usefulness and perceived ease of use, whereas the Ducoffe Model suggests that attitude can be shaped prior to usage experience through informativeness, entertainment, and irritation. The study employs Structural Equation Modeling–Partial Least Squares (SEM-PLS), using SmartPLS 4.0 as the analytical tool. Data were collected through questionnaires distributed directly to respondents using purposive sampling. The respondents were working individuals who made independent purchase decisions, used smartphones, had downloaded the Tokopedia mobile application, and had previously compared prices in conventional stores before shopping on Tokopedia. The results indicate that informativeness, entertainment, and irritation have significant effects on attitude toward the mobile application, which subsequently influences users’ intention to return. These findings support the applicability of the Ducoffe Model in the context of digital marketplace applications.